Identification of models of the labor Market - Eric French; Christopher Taber (Federal Reserve Bank of Chicago, 2010)
This chapter discusses identification of common selection models of the labor market. We start with the classic Roy model and show how it can be identified with exclusion restrictions. We then extend the argument to the generalized Roy model, treatment effect models, duration models, search models, and dynamic discrete choice models. In all cases, key ingredients for identification are exclusion restrictions and support conditions.
Keywords: C14; C51; J22; J24; 330; identification; Roy model; discrete choice; selection; treatment effects